2007
DOI: 10.1177/0960327107083453
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of estrogen-regulated gene expression in human cells induced by the agricultural and horticultural herbicide glyphosate

Abstract: Gene expression is altered in mammalian cells (MCF-7 cells), by exposure to a variety of chemicals that mimic steroid hormones or interact with endocrine receptors or their co-factors. Among those populations chronically exposed to these endocrine disruptive chemicals are persons, and their families, who are employed in agriculture or horticulture, or who use agricultural/horticultural chemicals. Among the chemicals most commonly used, both commercially and in the home, is the herbicide glyphosate. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…Glyphosate has been suggested to act as an estrogen agonist based on assays in cultures of human breast cancer cells at comparable concentrations to the native hormone3738. Other studies, albeit at much higher doses, have also shown that glyphosate can uncouple liver mitochondrial oxidative phosphorylation10.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate has been suggested to act as an estrogen agonist based on assays in cultures of human breast cancer cells at comparable concentrations to the native hormone3738. Other studies, albeit at much higher doses, have also shown that glyphosate can uncouple liver mitochondrial oxidative phosphorylation10.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reproducibility and the relevance for in vivo situations need to be confirmed by other studies. Alterations of estrogenic gene expression have also been demonstrated in another study investigating transcriptome responses of mammary cells to a GlyBH at higher levels (Hokanson et al, 2007). In another study, glyphosate and Roundup induced similar proliferative effects on MCF-7 mammary cells in both normal and charcoal-dextran-treated fetal bovine serum, suggesting a non-estrogenic mechanism of proliferation (Lin and Garry, 2000).…”
Section: Tumorigenicity and Carcinogenicitymentioning
confidence: 73%
“…Finally, it inhibits testosterone synthesis both in vitro on fresh adult rat isolated testicular cells (Clair et al, 2012) and in vivo in rats (Romano et al, 2010) from 5 mg/kg bw/d, it also disrupted testicular aromatase mRNA levels, among other markers (Cassault-Meyer et al, 2014). In a transcriptomic study in MCF7 mammary human cells, a GlyBH altered estrogen-regulated gene expressions and intracellular responses to hypoxia from 2.3 ppm glyphosate (Hokanson et al, 2007). It also inhibits the transcriptional activities of both androgen and estrogen receptors (Gasnier et al, 2009) from 0.5 mg/L Roundup (containing 0.2 mg/L G).…”
Section: In Human Fresh Cells or Cell Lines (Table 2) Some Endocrinementioning
confidence: 99%
See 1 more Smart Citation
“…EPA, 1993). Regulatory studies show that glyphosate per se is practically harmless to humans, wildlife and the environment; however, recent research indicates other ingredients in the formulation increase the toxicity and availability of glyphosate in mammalian (including human) cells, tissues and organs, raising concerns about the safety of glyphosate (Axelrad et al, 2003;Benachour and Séralini, 2009;Dallegrave et al, 2007;Hokanson et al, 2007;Richard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%